2016
DOI: 10.1038/nbt.3754
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide mapping of autonomous promoter activity in human cells

Abstract: Previous methods to systematically characterize sequence-intrinsic activity of promoters have been limited by relatively low throughput and the length of sequences that could be tested. Here we present Survey of Regulatory Elements (SuRE), a method to assay more than 108 DNA fragments, each 0.2–2kb in size, for their ability to drive transcription autonomously. In SuRE, a plasmid library is constructed of random genomic fragments upstream of a 20bp barcode and decoded by paired-end sequencing. This library is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

17
168
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(188 citation statements)
references
References 51 publications
17
168
2
1
Order By: Relevance
“…A number of studies have measured the ability of different genomic elements to function as either enhancers or promoters using massively parallel cell culture-based reporter assays. Measuring promoter activity of thousands of small DNA elements (Nguyen et al 2016) or across the entire human genome (van Arensbergen et al 2017) suggests that many enhancers (as well as repetitive elements) can act as weak autonomous promoters, although at levels ∼10-fold lower than that of annotated gene promoters. Conversely, testing promoters for enhancer activity revealed that ∼3% of human elements (Dao et al 2017) and 4.5% of Drosophila elements (Arnold et al 2013) spanning promoters have in vitro enhancer activity.…”
mentioning
confidence: 99%
“…A number of studies have measured the ability of different genomic elements to function as either enhancers or promoters using massively parallel cell culture-based reporter assays. Measuring promoter activity of thousands of small DNA elements (Nguyen et al 2016) or across the entire human genome (van Arensbergen et al 2017) suggests that many enhancers (as well as repetitive elements) can act as weak autonomous promoters, although at levels ∼10-fold lower than that of annotated gene promoters. Conversely, testing promoters for enhancer activity revealed that ∼3% of human elements (Dao et al 2017) and 4.5% of Drosophila elements (Arnold et al 2013) spanning promoters have in vitro enhancer activity.…”
mentioning
confidence: 99%
“…This is now possible using either of the new methods---self-transcribing active core promoter-sequencing (STAP-seq) by Arnold et al 7 ( Fig. 1a) and survey of regulatory elements (SuRE) by van Arensbergen et al 8 (Fig. 1b).…”
mentioning
confidence: 99%
“…The authors construct a candidate libraryand use it to assess sequence-intrinsic core promoter strength and promoter potential of candidate regions that span the entire Drosophila genome (Figure 1a In the second paper, van Arensbergen et al 8 introduce SuRE, which similarly queries the autonomous promoter activity of random genomic fragments outside of their genomic context using a defined reporter assay. One important difference relative to STAP-seq is the size of the tested fragments: to allow the entire human genome to be probed at high coverage, A limitation of SuRE compared to STAP-seq is lower resolution: the peaks obtained correspond in size to the tested fragments, whereas STAP-seq maps initiation start sites at single-nucleotide resolution.…”
mentioning
confidence: 99%
See 2 more Smart Citations